1998
DOI: 10.1016/s0735-1097(97)00432-4
|View full text |Cite
|
Sign up to set email alerts
|

Heart Disease From Passive Smoking in the Workplace

Abstract: The RRs for heart disease from passive smoking at work are roughly equal to those from home-based exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 25 publications
2
36
0
4
Order By: Relevance
“…Tobacco smoking has a pressing effect on the vessels, resulting in the development of arterial hypertension. Results of meta-analyses performed by several independent research centres have revealed a connection between passive smoking and CVD [20][21][22][23][24][25]. Low level of physical activity was the next problem in the population examined in our study; 46% of the participants (42% men and 54% women) did not practise any kind of physical activity during leisure time.…”
Section: Psychological Factorsmentioning
confidence: 68%
“…Tobacco smoking has a pressing effect on the vessels, resulting in the development of arterial hypertension. Results of meta-analyses performed by several independent research centres have revealed a connection between passive smoking and CVD [20][21][22][23][24][25]. Low level of physical activity was the next problem in the population examined in our study; 46% of the participants (42% men and 54% women) did not practise any kind of physical activity during leisure time.…”
Section: Psychological Factorsmentioning
confidence: 68%
“…Several reports, including 2 recent separate meta-analyses of 17 and 18 individual studies, assessed the association of SHS with heart disease. 20,[51][52][53] Both estimated that nonsmoking spouses of smoking partners experience an approximately 25% (95% confidence interval [CI] 17% to 32%) increased risk of heart disease. 52,53 A review of 6 studies examining the association between SHS in the workplace and cardiovascular disease noted that although none of the studies individually reached the level of a significant association (PϽ0.05), there was a positive association in 5 of the 6 studies and a significant exposureresponse relation between the intensity of SHS (measured by the number of cigarettes smoked by coworkers) and coronary risk in 2 of 3 studies that examined the trend.…”
Section: Secondhand Smokementioning
confidence: 99%
“…Based on pooled analyses of epidemiologic studies, nonsmokers exposed to ETS in the workplace have an estimated cardiovascular risk 1.35 times that of those not exposed, whereas those exposed at home have a cardiovascular risk 1.23 times that of the unexposed (4). Should these estimates be accurate, ETS exposure would rank as the third leading cause of avoidable death in the United States (1).…”
Section: Introductionmentioning
confidence: 99%